Foxs Knob the highest point of land - Branch Cultural Historical Association (2007)
There are many different types of hills in and around Branch knobs, hommocks, pinnacles, lookouts, knaps - each with their own characteristics and uses. The Foxs Knob is the highest point of land on the west side of St. Marys Bay. Hills are great places to get your bearings when travelling the woods. Like other areas of high, dry ground, the Foxs Knob provides ideal habitat for fox resting sites and breeding dens, as well as roosting places for partridge. Other hills around Branch include the Grassy Hommock, the Lookout, Mullowneys Hill, Drohans Lookout and Open Out the Fish Houses.